2012
DOI: 10.1262/jrd.11-094k
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Interferon-stimulated Genes and Interleukin-10 in Peripheral Blood Immune Cells During Early Pregnancy in Dairy Cows

Abstract: Abstract. In cows, interferon-tau (IFNT) regulates maternal recognition around days 15-19 after artificial insemination (AI). The present study hypothesized that if key target genes of IFNT are clearly upregulated in earlier stages of pregnancy, these genes could be use as indices of future pregnancy in cows. Therefore, we determined the expression of these genes in peripheral blood mononuclear leukocytes (PBMCs) and polymorphonuclear granulocytes (PMNs) during the maternal recognition period (MRP). Twenty mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 38 publications
5
71
1
2
Order By: Relevance
“…In contrast, Shirasuna et al (2012) did not observe any change in expression pattern of ISG15 in pregnant and non-pregnant cows 25 . In a study conducted in cow, the ISG15 expression was shown to be significantly up-regulated on day 17 of the pregnancy 21 .…”
Section: Interferon Stimulated Gene 15 (Isg15) Ubiquitin-like Modifiermentioning
confidence: 56%
See 1 more Smart Citation
“…In contrast, Shirasuna et al (2012) did not observe any change in expression pattern of ISG15 in pregnant and non-pregnant cows 25 . In a study conducted in cow, the ISG15 expression was shown to be significantly up-regulated on day 17 of the pregnancy 21 .…”
Section: Interferon Stimulated Gene 15 (Isg15) Ubiquitin-like Modifiermentioning
confidence: 56%
“…The OAS1 expression was amplified during days 15-18 in heifers 36 and cow 37 . Shirasuna et al (2012) documented that, the OAS1 expression did not vary in pregnant and nonpregnant cows 25 . The OAS1 mRNA expression was elevated within 24-48 h in PBMCs after initial signalling of IFNT in pregnant ewes 16 .…”
Section: '-5' Oligoadenylate Synthetase (Oas1)mentioning
confidence: 83%
“…Therefore real-time PCR analyses of ISG mRNA expression were run with different populations of circulating cells. Expression of ISG (ISG15, MX1, MX2) has been already described in PBMC (Shirasuna et al, 2012;Kizaki et al, 2013;Pugliesi et al, 2014), and in leucocytes (Yankey et al, 2001;Gifford et al, 2007;Green et al, 2010a). Kinetics of ISG expression level during peri-implantation was shown to be similar in PBMC and PMN (Shirasuna et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Expression of ISG (ISG15, MX1, MX2) has been already described in PBMC (Shirasuna et al, 2012;Kizaki et al, 2013;Pugliesi et al, 2014), and in leucocytes (Yankey et al, 2001;Gifford et al, 2007;Green et al, 2010a). Kinetics of ISG expression level during peri-implantation was shown to be similar in PBMC and PMN (Shirasuna et al, 2012). Kizaki et al (2013) demonstrated that ISG mRNA expression during early pregnancy is higher in granulocytes (eliminated during Percoll processing) than in monocytes and lymphocytes.…”
Section: Discussionmentioning
confidence: 93%
“…In uterus, IFNT acts in a paracrine manner to prevent expression of estrogen receptor alpha and oxytocin receptor in endometrial luminal epithelium and superficial glandular epithelium, thereby altering release of luteolytic pulses of PGF (Spencer et al, 2007b). Interferon-tau also stimulates expression of specific genes, termed interferon-stimulated genes (Antoniazzi et al, 2013), in the uterus (Johnson et al, 1999) and in peripheral tissues such as the CL (Oliveira et al, 2008;Bott et al, 2010) and peripheral blood cells (Gifford et al, 2007;Shirasuna et al, 2012). Thus, circulating IFNT that escapes the uterine lumen might prevent CL regression by acting directly on CL and this action could be independent or synergistic with the actions of IFNT on uterine PGF secretion.…”
Section: Period II Blockade Of Luteolysis In Early Pregnancyday 18-2mentioning
confidence: 99%